Removal of Fe (II) ions from Aqueous solution using Rice-husk Adsorbents in fixed-bed column - Rosnelly, Cut Meurah; Meiriza, Lia Meiriza -; Husin, Husni -; Zaki, Muhammad -; E, Muhammad Aqilussalim; Maliki, Syariful -; Aflah, Nurul -; El-Bahy, Zeinhom M (Jurnal Rekayasa Kimia & Lingkungan, 2021)
Rice husk has been converted into activated carbon for the adsorbent to remove the heavy metal from the aqueous solution. This study aimed to convert rice husk to activated carbon (AC) for use in the adsorption of Fe ions in a fixed-bed column. Rice husk was first pyrolyzed in an atmosphere of nitrogen gas at 400 oC, then a chemical activation method using sodium hydroxide. The rice husk activated carbon (RH-AC) was characterized using Fourier transform infrared (FTIR) and Scanning electron microscope (SEM) to identify the functional group and microstructure of carbon. The performance of the carbon was tested on the Fe removal from an aqueous solution in a continuous column. The adsorption process was carried out using Fe solution with an initial concentration of 3 mg/L as an artificial sample. The amount of carbon is 25, and 50 g were filled in an adsorber column with a diameter of 5.4 cm and height of 40 cm. SEM images revealed that the activated carbons shown with well-developed pore sizes and pore structure were produced after the chemical activation. The FTIR absorption bands observed in the RH-AC sample confirmed the presence of hydroxyl (-OH), carbonyl, and carboxylic (-COOH) groups of RH-AC adsorbent. The highest Fe removal efficiencies were 91.9% on chemically activated carbon and column mass 50 g at 400 minutes. The overall study revealed the potential value of chemically activated RH-AC as a possible commercial adsorbent in a continuous column wastewater treatment strategy.